Prevalence of anxiety in patients admitted to a university hospital in southern Brazil and associated factors - Inês Gullich; Andrews Barcellos Ramos; Tiago Rafael Anschau Zan; Cíntia Scherer; Raúl Andrés Mendoza-Sassi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Objective: To identify the prevalence of anxiety in adults hospitalized in the clinical ward of a university hospital and to analyze the possible associated factors. Method: A cross-sectional study was performed in a university hospital. All interviewees answered a specific questionnaire and the Hospital Anxiety and Depression Scale. A Poisson regression was used to calculate prevalence ratios with 95% confidence intervals. Results: 282 patients were enrolled. The prevalence of anxiety was 33.7% (95%CI 28.2 - 39.3). Characteristics associated with the outcome were female gender (RP 2.44), age ≥ 60 years (PR 0.65), consultation in primary health care (PR 2.37), estimated time of contact between patient and student > 30 min (RP 1.36), high blood pressure (PR 1.57), diabetes mellitus (PR 1.43), and obesity (RP 1.43). Conclusion: This study found prevalence of high anxiety. It may be associated with certain characteristics of the patients (gender, age, chronic diseases); the medical appointment in primary care and time (estimated by the patient) that the student remained with this patient. The need for a focused approach to mental health care within the hospital has been discussed for a long time. The particularity of this study refers to the environment of a university hospital and to what extent the environment and the patient's relationship with the student are associated with higher prevalence of anxiety.